Legal Measure for Air Pollution control in Thailand : Study the Effective Process Prevention, Control and Correction or Disposal of Particulate Matter Not More Than 2.5 Microns (PM2.5) in Foreign Countries - กิติภูวดล วริศรา (CRRU Law, Political Science and Social Science Journal, 2021)
Nowadays, Thailand is faced with a problem of particulate pollutants that are 2.5 microns or smaller in size (PM 2.5) that cause by the dust form burning of agricultural waste and the forest fire in the north of Thailand And dust from transportation and construction in Bangkok. The problem of air pollution in Thailand are extensive and could become more seriously in the future. If there is no effective solution to the problem, It may cause damages on economic, Society and on the health of the people in the country. To find solutions to these problems, an international comparative legal study was made of measures to prevent, control, correct and remove PM 2.5 by relevant agencies as well as laws in the United States of America (USA) and Singapore, to provide problem-solving guidelines. Results were that Thailand’s Enhancement and Conservation of the National Environmental Quality Act, B.E. 2535 (1992) contained insufficiently comprehensive legal measures to prevent, control, correct, and dispose of PM 2.5. These findings suggest that current legal measures in Thailand should be amended to manage PM 2.5 aerosol particle problems more efficiently.